Effects of surface instability on neuromuscular performance during drop jumps and landings - Prieske, O.; Muehlbauer, T.; Mueller, S.; Krueger, T.; Kibele, A.; Behm, D. G.; Granacher,U. (European Journal of Applied Physiology, 2013)
Purpose The purpose of this study was to investigate the effects of surface instability on measures of performance and activity of leg and trunk muscles during drop jumps and landings. Methods Drop jumps and landings were assessed on a force plate under stable and unstable (balance pad on top of the force plate) conditions. Performance measures (contact time, jump height, peak ground reaction force) and electromyographic (EMG) activity of leg and trunk muscles were tested in 27 subjects (age 23 ± 3 years) during different time intervals (preactivation phase, braking phase, push-off phase). Results The performance of drop jumps under unstable compared to stable conditions produced a decrease in jump height (9 %, p < 0.001, f = 0.92) and an increase in peak ground reaction force (5 %, p = 0.022, f = 0.72), and time for braking phase (12 %, p < 0.001, f = 1.25). When performing drop jumps on unstable compared to stable surfaces, muscle activity was reduced in the lower extremities during the preactivation, braking and push-off phases (11-25 %, p < 0.05, 0.48 ? f ? 1.23). Additionally, when landing on unstable compared to stable conditions, reduced lower limb muscle activities were observed during the preactivation phase (7-60 %, p < 0.05, 0.50 < f < 3.62). Trunk muscle activity did not significantly differ between the test conditions for both jumping and landing tasks. Conclusion The present findings indicate that modified feedforward mechanisms in terms of lower leg muscle activities during the preactivation phase and/or possible alterations in leg muscle activity shortly after ground contact (i.e., braking phase) are responsible for performance decrements during jumping on unstable surfaces.